Peningkatan Pembelajaran Tematik dengan Pendekatan Scientific di Kelas I SDN 15 Ulu Gadut Kota Padang - Purnamasari, Juita; Yunisrul, Yunisrul; Desyandri, Desyandri (Universitas Negeri Padang, 2014)
The purpose of this study is to describe the application of integrated thematic learning by using science in Class I SDN 15 Ulu Gadut Padang. This type of research is Classroom Action Research and using qualitative and quantitative approach. Data source is the data process of the implementation of integrated thematic learning by using a scientific approach. The results showed that the value of learning cycle planning 1 meeting was 69,4% (enough), II meeting was 75% (good) and increased cycle II 88,9% (very good). The result of observation on the aspects of teacher cycle 1 meeting I 58.33% (less), meeting II 75% (enough) and increased cycle II 95% (very good). The result of observation of student aspects of the 1st cycle of meeting I 55% (less), meeting II 75% (enough) and 95% increase (95%) excellent cycle. In each cycle, it is shown that the improvement of students' learning outcomes in cycle I meeting 1 on average is 2.6 (enough), meeting 2 is 3.0 (good) and cycle II is 3,3 (very good). Can be concluded in the study that learning using scintific approach can improve student learning outcomes in school.